A starch-based hard carbon material, a preparation method and application thereof

CN118306977BActive Publication Date: 2026-10-30CNBM ZHEJIANG MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410541244.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-30
Publication Date
2026-10-30
Estimated Expiration
2044-04-30

AI Technical Summary

Technical Problem

空气氧化法是一种常用的工业氧化法,但直接在空气气氛下对淀粉进行预氧化,氧化效果有限且操作安全性、批次稳定性均难以保证,专利文件CN114436237A公开在空气氛围下配合微波处理将硬碳前驱体中引入含氧官能团;专利文件CN116253306A公开在一次烧结后使用KMnO4溶液、NaClO溶液、H2O2溶液、Na2S2O8溶液中进行液相预氧化引入含氧官能团,再做微波处理,虽然提高了硬碳材料的电化学性能,但工艺复杂,使用微波操作能耗较大,与工业现有产线匹配度不高,生产成本优势不大

Benefits of technology

[0027]本申请还提供了一种淀粉基硬碳材料,由上文所述的制备方法所制得,其可逆容量至少为265mAh/g,首次库伦效率至少为81%。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118306977B_ABST
    Figure CN118306977B_ABST
Patent Text Reader

Abstract

The application discloses a starch-based hard carbon material and a preparation method and application thereof, and a preparation method of the starch-based hard carbon material, which comprises the following steps: S1, adding a starch-based hard carbon precursor into an oxidizing agent to perform pre-oxidation treatment, to obtain a first precursor; S2, performing first heat treatment on the first precursor, crushing and sieving to obtain a second precursor; and S3, performing second heat treatment on the second precursor, to obtain the starch-based hard carbon material. The preparation method of the starch-based hard carbon material provided in the application can cross-link starch molecules with each other by adding an oxidizing agent to perform pre-oxidation treatment, so that expansion of the starch molecules in the calcination process is avoided, and in addition, the use of the oxidizing agent can also graft rich oxygen-containing functional groups (such as C-O, C=O and the like), so that the sodium storage capacity is improved; and the preparation process is simple and easy to implement, the required equipment has high matching degree with a current process line, and has certain cost advantages; and the starch-based hard carbon material prepared has good electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of sodium-ion battery anode material technology, and in particular to a starch-based hard carbon material, its preparation method and application. Background Technology

[0002] Hard carbon is characterized by its disordered internal crystal arrangement and large interlayer spacing, which allows it to store more charge in the same volume and is beneficial for Na+. + The extraction and insertion of starch are considered promising anode materials for sodium-ion batteries and have been extensively studied in recent years. Starch is one of the most abundant recycled biomaterials, with a simple composition, high carbon content, and low cost, making it an excellent precursor for producing hard carbon. However, direct carbonization of starch often results in puffing, which is unfavorable for industrial production. The resulting hard carbon has a large specific surface area, low initial coulombic efficiency, and low sodium storage capacity.

[0003] The oxygen content of the precursor has a certain impact on the electrochemical performance of hard carbon anode materials. The electrochemical performance of hard carbon anode materials can be improved by increasing the oxygen content of the precursor through oxidation. Air oxidation is a commonly used industrial oxidation method, but directly pre-oxidizing starch in an air atmosphere has limited oxidation effect and makes it difficult to guarantee operational safety and batch stability. Patent document CN114436237A discloses introducing oxygen-containing functional groups into the hard carbon precursor through microwave treatment in an air atmosphere; patent document CN116253306A discloses introducing oxygen-containing functional groups through liquid-phase pre-oxidation using KMnO4 solution, NaClO solution, H2O2 solution, and Na2S2O8 solution after a single sintering, followed by microwave treatment. Although this improves the electrochemical performance of hard carbon materials, the process is complex, the energy consumption of microwave operation is high, and it is not well-matched with existing industrial production lines, resulting in little cost advantage. Summary of the Invention

[0004] To address the aforementioned issues, this application provides a method for preparing hard carbon that is simple to produce, safe to operate, and has controllable batch stability, resulting in hard carbon materials with excellent electrochemical properties.

[0005] This application discloses a method for preparing a starch-based hard carbon material, comprising the following steps:

[0006] S1. Add an oxidant to the starch-based hard carbon precursor for pre-oxidation treatment to obtain the first precursor;

[0007] S2. The first precursor is subjected to a first heat treatment, crushed and sieved to obtain the second precursor.

[0008] S3. The second precursor is subjected to a second heat treatment to obtain starch-based hard carbon material.

[0009] The starch-based hard carbon precursor is selected from at least one of legume starch, potato starch, cereal starch, water chestnut starch, and lotus root starch.

[0010] Furthermore, in step S1, the pre-oxidation treatment involves mechanically mixing the starch-based hard carbon precursor and the oxidant until homogeneous, followed by calcination in an air atmosphere.

[0011] The oxidant is directly mixed with the starch-based hard carbon precursor and then calcined in air for pre-oxidation treatment. No microwave treatment is required. The pre-oxidation process is simple, safe and under controllable conditions, which makes the batch-to-batch stability of starch-based hard carbon materials controllable.

[0012] Furthermore, in step S1, the roasting temperature is 150–300°C, preferably 180–200°C, and the roasting time is 2–4 hours.

[0013] A suitable oxidation temperature is beneficial for the oxidation and cross-linking of starch-based hard carbon precursors, thereby preventing starch from expanding during calcination. Too low a calcination temperature will prevent the oxidation process from taking place, while too high a oxidation temperature can easily lead to over-oxidation of the starch-based hard carbon precursor, resulting in an excessively large specific surface area of ​​the produced starch-based hard carbon, which affects the initial efficiency and compaction density.

[0014] Furthermore, in step S1, the mechanical mixing method is ball milling or high-speed agitator, preferably ball milling, with the ball milling speed controlled at 100-500 r / min and the mixing time at 0.5-2 h.

[0015] Furthermore, in step S1, the mechanical mixing method is ball milling or high-speed agitator, and the mixing time is 0.5 to 3 hours.

[0016] Furthermore, in step S1, the oxidant is selected from at least one of sodium persulfate, ammonium persulfate, potassium persulfate, sodium percarbonate, sodium perborate, hydrogen peroxide, nitric acid, sulfuric acid, potassium permanganate, potassium dichromate, sodium hypochlorite, and potassium hypochlorite.

[0017] Adding an oxidant introduces oxygen-containing functional groups into the original structure of the starch hard carbon precursor. The introduction of oxygen-containing functional groups can significantly improve the sodium storage performance of hard carbon materials, thereby obtaining a higher sodium storage capacity.

[0018] The pre-oxidation process enables the oxidation and cross-linking of starch-based hard carbon materials, preventing the materials from expanding during carbonization.

[0019] The oxidants include solid-phase oxidants and liquid-phase oxidants. Solid-phase oxidants (such as sodium persulfate, ammonium persulfate, potassium persulfate, sodium percarbonate, sodium perborate, potassium permanganate, potassium dichromate, sodium hypochlorite, and potassium hypochlorite) directly oxidize the precursor. Liquid-phase oxidants (such as hydrogen peroxide, nitric acid, and sulfuric acid) need to be prepared into solutions of appropriate concentrations to oxidize the precursor, for example, a concentration of 1 mol / L.

[0020] Furthermore, the oxidant is selected from at least one of ammonium persulfate and sodium perborate.

[0021] Using ammonium sulfate and sodium perborate can also achieve the doping of heteroatoms during the pre-oxidation process. Ammonium persulfate contains S and N, and sodium perborate contains B, which are heteroatoms. The addition of heteroatoms can adsorb sodium ions, promote electrochemical reactions, expand the interlayer spacing of hard carbon, and thus increase the sodium storage capacity.

[0022] Furthermore, in step S1, the molar amount of the oxidant is (0.8-1.5) mol: 100 g for the mass of the starch-based hard carbon precursor.

[0023] The oxygen-containing functional groups and heteroatoms generated during pre-oxidation will adsorb sodium ions during charge and discharge, increasing sodium storage capacity; however, excessive oxidation will lead to an increase in specific surface area, reducing initial efficiency. Controlling the amount of oxidant added within this range can not only improve initial efficiency but also improve reversible capacity.

[0024] Furthermore, in step S2, during the first heat treatment, a protective gas is introduced, the temperature is controlled at 350–600°C, the heating rate is 0.5–20°C / min, and the holding time is 1–4 hours. For example, the protective gas is nitrogen.

[0025] Furthermore, in step S3, during the second heat treatment, a protective gas is introduced, the temperature is controlled at 1100–1400°C, the heating rate is 0.5–10°C / min, and the holding time is 1–4 hours. For example, the protective gas is argon.

[0026] The second heat treatment, by controlling the heating rate, aims to increase the specific surface area of ​​the hard carbon material from 100 to 200 m² while maintaining the favorable structure of the starch-based hard carbon precursor for the electrochemical performance of sodium-ion batteries. 2 / g decreased to 10m 2 Within / g, the specific surface area of ​​starch-based hard carbon materials is significantly reduced. The larger specific surface area of ​​starch-based hard carbon materials leads to the formation of a larger SEI film during the first charge-discharge cycle. This process consumes sodium ions, affecting electrochemical performance. Reducing the specific surface area of ​​starch-based hard carbon materials improves their electrochemical performance.

[0027] This application also provides a starch-based hard carbon material prepared by the preparation method described above, which has a reversible capacity of at least 265 mAh / g and an initial coulombic efficiency of at least 81%.

[0028] This application also provides a sodium-ion battery, including the starch-based hard carbon material described above.

[0029] This application provides a starch-based hard carbon material and its preparation method. Pre-oxidation treatment with an oxidant can cross-link starch molecules, thereby preventing them from expanding during calcination. In addition, the use of an oxidant can also graft abundant oxygen-containing functional groups (such as CO, C=O, etc.), improving sodium storage capacity. Furthermore, the preparation process is simple and easy to implement, and the required equipment is highly compatible with current process lines, resulting in a certain cost advantage. The obtained starch-based hard carbon material exhibits good electrochemical performance. Attached Figure Description

[0030] Figure 1 Scanning electron microscope image of starch-based hard carbon material prepared in Example 3;

[0031] Figure 2 Charge-discharge curves of starch-based hard carbon materials prepared in Example 3. Detailed Implementation

[0032] The following detailed description of the embodiments of this application, in conjunction with the accompanying drawings, will provide a thorough understanding of how this application uses technical means to solve technical problems and achieve technical effects, enabling its implementation accordingly. All other embodiments obtained by those skilled in the art based on the embodiments of this application without inventive effort are within the scope of protection of this application.

[0033] The reagents, methods, and equipment used in this application are conventional in this technical field. Unless otherwise specified, all reagents and materials used in this application are commercially available.

[0034] Example 1

[0035] S1: Weigh 5.00g of corn starch and 10mL of 1mol / L sulfuric acid solution and place them in a ball mill jar. Adjust the speed to 300r / min and process for 1h. After mixing evenly, dry the resulting mixture in an 80℃ oven and then place it in a tube furnace. In an air atmosphere, adjust the temperature to 200℃ and calcine for 3h. After calcination, the first precursor is obtained.

[0036] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0037] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1200℃ at 0.5℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0038] Example 2

[0039] S1: Weigh 5.00g of sweet potato starch and 1.2g of sodium perborate powder and place them in a ball mill jar. Adjust the speed to 400r / min and process for 1h to mix evenly. Then place the resulting mixture in a tube furnace and calcine at 180℃ in an air atmosphere for 3.5h. After calcination, the first precursor is obtained.

[0040] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 400℃ at 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0041] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1300℃ at 0.5℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0042] Example 3

[0043] S1: Weigh 5.00g of corn starch and 2.3g of ammonium persulfate powder into a ball mill jar, adjust the speed to 200r / min, process for 1h, mix evenly, place the resulting mixture into a tube furnace, adjust the temperature to 200℃ in an air atmosphere, calcine for 2h, and the first precursor is obtained after calcine is completed.

[0044] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at a rate of 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0045] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1200℃ at a rate of 0.5℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0046] Example 4

[0047] In this example, mechanical stirring was not used in the pre-oxidation step. The specific steps are as follows:

[0048] S1: Weigh 5.00g of potato starch and mix it with 10mL of 1mol / L H2O2 solution. Dry the resulting mixture in an 80℃ oven and then place it in a tube furnace. Under an air atmosphere, adjust the temperature to 150℃ and calcine for 4 hours. After calcine is completed, the first precursor is obtained.

[0049] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0050] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1100℃ at 0.5℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0051] Example 5

[0052] S1: Weigh 5.00g of corn starch and 10mL of 1mol / L H2O2 solution and place them in a ball mill jar. Adjust the speed to 350r / min and process for 1h. After mixing evenly, dry the resulting mixture in an 80℃ oven and then place it in a tube furnace. In an air atmosphere, adjust the temperature to 250℃ and calcine for 2.5h. After calcination, the first precursor is obtained.

[0053] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at a rate of 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0054] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1400℃ at a rate of 0.5℃ / min and held at that temperature for 1.5h. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0055] Example 6

[0056] S1: Weigh 5.00g of corn starch and 10mL of 1mol / L H2O2 solution and place them in a ball mill jar. Adjust the speed to 200r / min. After mixing evenly, dry the resulting mixture in an 80℃ oven and then place it in a tube furnace. In an air atmosphere, adjust the temperature to 150℃ and calcine for 3h. After calcination, the first precursor is obtained.

[0057] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 300℃ at 1℃ / min and held for 2h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0058] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, and argon protective gas is introduced. The temperature is increased to 1300℃ at 15℃ / min and held for 3.5h. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0059] Example 7

[0060] S1: Weigh 5.00g of corn starch and 4.3g of ammonium persulfate powder into a ball mill jar, adjust the speed to 400r / min, process for 1h, mix evenly, place the resulting mixture into a tube furnace, adjust the temperature to 200℃ in an air atmosphere, calcine for 3h, and the first precursor is obtained after calcine is completed;

[0061] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 500℃ at a rate of 1℃ / min and held for 2.5h, cooled to room temperature and taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0062] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1300℃ at a rate of 3℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0063] Example 8

[0064] S1: Weigh 5.00g of corn starch and 0.5g of ammonium persulfate powder into a ball mill jar, adjust the speed to 500r / min, process for 1h, mix evenly, place the resulting mixture into a tube furnace, adjust the temperature to 200℃ in an air atmosphere, calcine for 3h, and the first precursor is obtained after calcine is completed.

[0065] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at a rate of 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0066] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1300℃ at a rate of 0.5℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0067] Example 9

[0068] S1: Weigh 5.00g of corn starch and 1.2g of sodium perborate powder into a ball mill jar, adjust the speed to 450r / min, process for 1h, mix evenly, place the resulting mixture in a tube furnace, adjust the temperature to 100℃ in an air atmosphere, calcine for 3h, and the first precursor is obtained after calcine is completed.

[0069] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 550℃ at a rate of 1℃ / min and held for 1.5h, cooled to room temperature and taken out, crushed and sieved so that the powder particle size is between 10 and 15μm, to obtain the second precursor.

[0070] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1300℃ at a rate of 2℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0071] Example 10

[0072] S1: Weigh 5.00g of corn starch and 1.2g of sodium perborate powder into a ball mill jar, adjust the speed to 350r / min, process for 1h, mix evenly, place the resulting mixture into a tube furnace, adjust the temperature to 350℃ in an air atmosphere, calcine for 3h, and the first precursor is obtained after calcine is completed.

[0073] S2: The first precursor obtained in S1 is placed in a tube furnace, nitrogen protective gas is introduced, the temperature is raised to 450℃ at a rate of 1℃ / min and held for 3h, and after cooling to room temperature, it is taken out, crushed and sieved so that the powder particle size is between 10 and 15μm to obtain the second precursor.

[0074] S3: The second precursor obtained in S2 is placed in a high-temperature tube furnace, purged with argon protective gas, heated to 1300℃ at a rate of 4℃ / min and held for 3 hours. After naturally cooling to room temperature, it is taken out to obtain starch-based hard carbon material.

[0075] Comparative Example 1

[0076] Step 1: Weigh 5.00g of corn starch, place it in a tube furnace, adjust the temperature to 200℃ in an air atmosphere, and calcine for 3 hours. After calcination, the first precursor is obtained.

[0077] Step 2: Place the first precursor in a tube furnace, purge with nitrogen protective gas, heat to 450°C at a heating rate of 1°C / min and hold for 3 hours. After cooling to room temperature, remove the precursor, crush and sieve it to make the powder particle size between 10 and 15 μm.

[0078] S2: Place the powder obtained in step 2 in a high-temperature tube furnace, pass argon protective gas through it, heat it to 1300℃ at a rate of 0.5℃ / min and hold it at that temperature for 3 hours. After naturally cooling to room temperature, take it out to obtain starch-based hard carbon material.

[0079] Comparative Example 2

[0080] Weigh 5.00g of starch and place it in a high-temperature tube furnace. Purge with nitrogen protective gas and heat to 1400℃ at 1℃ / min. Hold at this temperature for 3 hours. After naturally cooling to room temperature, remove the material to obtain starch-based hard carbon material.

[0081] Performance testing

[0082] The starch-based hard carbon anode materials prepared in the above embodiments and comparative examples were subjected to charge-discharge specific capacity, specific surface area, pore size, and pore volume tests. The specific operations are as follows:

[0083] (1) Reversible capacity test:

[0084] The prepared starch-based hard carbon material was mixed with CMC and conductive carbon black in a mass ratio of 8:1:1 to form a slurry, which was then coated onto the current collector and dried. The slurry was then cut and rolled to obtain the sodium-ion battery negative electrode sheet, which was then sent to a glove box for assembly into button batteries. Testing was conducted using a CT200A Blue Electric multi-functional battery testing system, with a constant temperature of 30°C, constant current discharge to 0V at 0.1C, and then constant current charging to 2V.

[0085] (2) Specific surface area, pore size and pore volume test:

[0086] The prepared starch-based hard carbon material was characterized using a Micron ASAP1460 surface area and porosity analyzer. The sample was degassed under vacuum at 300℃ for 1 h, and then tested using N2 as the adsorbate.

[0087] The test results are shown in Table 1 below:

[0088] Table 1 Performance Test Results

[0089]

[0090] SEM images of the starch-based hard carbon material prepared in Example 3 of this application are shown below. Figure 1 As shown. From Figure 1 The starch-based hard carbon particles are uniform in size, less than 20 μm, and nearly spherical in shape with a smooth surface. This type of spherical starch-based hard carbon material has properties such as low porosity, good oxidation resistance, uniform and delicate structure, small void defects, and easy molding. It can effectively suppress side reactions, reduce polarization, and thus extend the battery's lifespan.

[0091] As shown in Table 1, compared to Comparative Examples 1-2, the starch-based hard carbon materials prepared in Examples 1-3 exhibit higher reversible capacity and first-pass efficiency, as well as lower specific surface area. The use of mechanical mixing during the pre-oxidation process significantly affects the electrochemical performance of the starch-based hard carbon anode. The addition of S and N-containing ammonium persulfate resulted in the highest reversible capacity and first-pass efficiency in the prepared starch-based hard carbon materials. The doping of heteroatoms further enhanced the electrochemical performance of the material. Figure 2 As shown, the starch-based hard carbon material prepared in Example 3 has a first-charge specific capacity of 366.8 mAh / g and a first-charge efficiency of 92.8%, exhibiting superior electrochemical performance.

[0092] Compared to Comparative Examples 1 and 6, the starch-based hard carbon materials prepared in Examples 2 and 3 have a lower specific surface area and a larger pore size. This is because controlling the heating rate during high-temperature calcination helps to reduce the specific surface area of ​​the material.

Claims

1. A method for preparing a starch-based hard carbon material, characterized in that, Includes the following steps: S1. Add an oxidant to the starch-based hard carbon precursor for pre-oxidation treatment to obtain the first precursor; S2. The first precursor is subjected to a first heat treatment, crushed and sieved to make the powder particle size between 10 and 15 μm, to obtain the second precursor. S3. The second precursor is subjected to a second heat treatment to obtain starch-based hard carbon material; In step S1, no crosslinking agent is added to the pre-oxidation treatment. In step S1, the pre-oxidation treatment involves mechanically mixing the starch-based hard carbon precursor and the oxidant until homogeneous, followed by calcination in an air atmosphere. In step S1, the oxidant is selected from at least one of sodium persulfate, ammonium persulfate, potassium persulfate, sodium percarbonate, sodium perborate, hydrogen peroxide, nitric acid, sulfuric acid, potassium permanganate, potassium dichromate, sodium hypochlorite, and potassium hypochlorite. In step S1, the mechanical mixing method is ball milling or high-speed agitator, and the mixing time is 0.5 to 2 hours; In step S2, during the first heat treatment, a protective gas is introduced, the temperature is controlled at 350–600℃, the heating rate is 0.5–20℃ / min, and the holding time is 1–4h; in step S3, during the second heat treatment, a protective gas is introduced, the temperature is controlled at 1100–1400℃, the heating rate is 0.5–10℃ / min, and the holding time is 1–4h. In step S1, the calcination temperature is 150–300℃ and the calcination time is 2–4 hours.

2. The method for preparing a starch-based hard carbon material according to claim 1, characterized in that, In step S1, the oxidant is selected from at least one of ammonium persulfate and sodium perborate.

Citation Information

Patent Citations

  • Hard carbon material and preparation method and application thereof

    CN114436237A

  • Sodium-ion battery hard carbon negative electrode material and preparation method and application thereof

    CN116253306A

  • Hard carbon negative electrode material, preparation method thereof and secondary battery

    CN115838165A